Comparison of the effect of acetazolamide tablets and sustets on diurnal intraocular pressure in patients with chronic simple glaucoma. - Joyce, P W (1990)
Twenty patients with primary open-angle glaucoma uncontrolled on single topical therapy completed a double dummy crossover study to compare acetazolamide tablets with a sustained release formulation (Sustet). The two preparations were equally effective, but no direct relationship was found between the intraocular pressure and the plasma concentration of acetazolamide. No difference between the formulations was found in the frequency or severity of side effects.